Local renal complement C3 induction by donor brain death is associated with reduced renal allograft function after transplantation. - Damman, J; Nijboer, W; Schuurs, T; Leuvenink, H; Morariu, A; Tullius, S; van Goor, H; Ploeg, R; Seelen, M (2011)
BACKGROUND: Kidneys derived from brain-dead donors have inferior outcomes after transplantation compared to kidneys from living donors. Strikingly, early and profound serum levels of IL-6 in brain-dead donors are observed. IL-6 is the main regulator of the acute phase response (APR). The aim of this translational study was to investigate the expression of renal acute phase proteins (APPs) following brain death (BD) and to assess the association with renal allograft outcome after transplantation. METHODS: BD was induced in rats by inflating a subdurally placed balloon catheter. Kidney biopsies were obtained from human living and brain-dead donors at donation, after cold preservation and reperfusion. In vitro, renal proximal tubular epithelial cells (HK-2 cells) were stimulated with IL-6. RESULTS: Both in human and rat brain-dead donors, C3 and FBG expression was enhanced at donation compared to living donors and sham-operated animals. In human donors, no additional expression was found after cold ischaemia or reperfusion. C3 expression after reperfusion was independently associated with decreased short-term function after transplantation in grafts from brain-dead donors. In cultured HK-2 cells, C3 production was induced in the presence of IL-6. CONCLUSIONS: In conclusion, BD induces renal C3 and FBG expression. Moreover, C3 expression is associated with a worse allograft function early after transplantation. Therefore, targeting renal APPs in brain-dead donors, especially complement C3, may improve transplant outcome.